Invasive Fungal Infections Secondary to Traumatic Injury. (September 2017) - Kronen, Ryan; Liang, Stephen Y.; Bochicchio, Grant; Bochicchio, Kelly; Powderly, William G.; Spec, Andrej
Highlights: Invasive fungal infection is a potentially serious complication of traumatic injury. Mucorales is the most common pathogen involved in post-traumatic IFI. Risk factors include injury type, receipt of a blood transfusion, and rhabdomyolysis. Early surgical debridement and antifungal therapy are the mainstays of treatment. Abstract: Invasive fungal infection (IFI) is a rare but serious complication of traumatic injury. The purpose of this article is to review the epidemiology, natural history, mycology, risk factors, diagnosis, treatment, and outcomes associated with post-traumatic IFI in military and civilian populations. The epidemiology of post-traumatic IFI is poorly characterized, but incidence appears to be rising. Patients often suffer from severe injuries and require extensive medical interventions. Fungi belonging to the order Mucorales are responsible for most post-traumatic IFI in both civilian and military populations. Risk factors differ between these cohorts but include specific injury patterns and comorbidities. Diagnosis of post-traumatic IFI typically follows positive laboratory results in the appropriate clinical context. The gold standard of treatment is surgical debridement in addition to systemic antifungal therapy. Patients with post-traumatic IFI may be at greater risk of amputation, delays in wound healing, hospital complications, and death as compared to trauma patients who do not develop IFI. More research is needed to understand the factors surrounding the development and management of post-traumatic IFI to reduce the significant morbidity and mortality associated with this disease.